Enhanced path smoothing based on conjugate gradient descent for firefighting robots in petrochemical complexes*. (18th July 2019) - Mizuno, Naoki; Ohno, Kazunori; Hamada, Ryunosuke; Kojima, Hiroyoshi; Fujita, Jun; Amano, Hisanori; Westfechtel, Thomas; Suzuki, Takahiro; Tadokoro, Satoshi
Abstract : The firefighting robot system (FFRS) comprises several autonomous robots that can be deployed to fire disasters in petrochemical complexes. For autonomous navigation, the path planner should consider the robot constraints and characteristics. Specifically, three requirements should be satisfied for a path to be suitable for the FFRS. First, the path must satisfy the maximum curvature constraint. Second, it must be smooth for robots to easily execute the trajectory. Third, it must allow reaching the target location in a specific heading. We propose a path planner that provides smooth paths, satisfy the maximum curvature constraint, and allows a suitable robot heading. The path smoother is based on the conjugate gradient descent, and three approaches are proposed for this path planner to meet all the FFRS requirements. The effectiveness of these approaches is qualitatively and quantitatively evaluated by examining the generated paths. Finally, the path planner is applied to an actual robot to verify the suitability of the generated paths for the FFRS, and planning is applied to another type of robot to demonstrate the wide applicability of the proposed planner. GRAPHICAL ABSTRACT: